Workshop on the Development of ICT-Assisted Teaching Materials for Teachers at MTs Darul Hikmah Pekanbaru - Istikomah, Endang; Yuliani, Sri; Widiati, Indah; Supriadi, Edi; Marnis, Eli; Irawan, Hendra; Azzahra, Lazira (UIR Press, 2025)
This community service activity aims to encourage teachers to utilize information and communication technology (ICT) to improve the use of learning methods, so that the learning process becomes more interactive and interesting through the development of ICT-assisted teaching materials at MTs Darul Hikmah Pekanbaru. This workshop involved 33 teachers and was held on November 30, 2024. The stages of the activity include preparation, implementation, discussion, and Q&A. This PkM activity succeeded in achieving its goal of motivating teachers to maximize the use of technology in learning through the development of teaching materials, even though there were challenges that had to be faced. The evaluation results showed a positive response from teachers.